I got the show right here the amazing, true story of how an obscure Brooklyn horn player became the last great Broadway showman - Feuer, Cy (Simon & Schuster, 2003)
A tour of Broadway during the mid-twentieth century traces the author's journey from a Brooklyn tenement district resident to one of New York's most successful producers.
"Producer of Guys & dolls, How to succeed in business without really trying, Can can, and many, many more legendary shows." -- Includes index.
Keywords: Feuer, Cy; Feuer, Cy -- 1911-2006; Conductors (Music) -- Biography; Musicals -- Production and direction -- New York (State) -- New York; Producers and directors -- New York (State) -- Biography; Theatrical producers and directors -- New York (State) -- New York -- Biography; Biografie